Impact of the number of involved lymph node zones on survival in stage IIIA-N2 lung adeno and squamous cell carcinoma - Griffo, Raffaella; Hoffmann, Hans; Safi, Seyer; Eichhorn, Florian; Klotz, Laura Valentina; Muley, Thomas; Baum, Philip; Kriegsmann, Mark; Bischoff, Helge; Winter, Hauke; Eichhorn, Martin E. (Interdisciplinary cardiovascular and thoracic surgery, 2025)
OBJECTIVES The role of upfront surgery in treating stage IIIA-N2 non-small cell lung cancer remains controversial. This study aimed to evaluate the role of upfront surgery in selected patients with stage IIIA-N2 and assess the prognostic significance of the number of involved lymph node zones in relation to the N2-subclassification proposed by the International Association for the Study of Lung Cancer, comparing adenocarcinoma and squamous cell carcinoma.METHODS We retrospectively analysed patients with pIIIA-N2 adeno- or squamous cell carcinoma who underwent complete surgical resection with zone-based lymph node dissection. Survival was calculated using the Kaplan-Meier method, and group differences were assessed via log-rank test and Cox regression analysis.RESULTS A total of 222 patients were analysed. The 5-year overall survival rate was 43%, with a median overall survival of 47.2 months. In the adenocarcinoma cohort, the N2b-subgroup was associated with a 1.7-fold increased risk of death, whereas adjuvant chemotherapy reduced the risk by 41%. In squamous cell carcinoma, neither adjuvant chemotherapy nor the N2b-subgroup were identified as prognostic factors for overall survival.CONCLUSIONS The zone concept for intraoperatively assigning lymph nodes and the proposed N2-subgroups allowed a good stratification of long-term survival in patients with adenocarcinoma. The role of surgery in the treatment of non-small cell lung cancer (NSCLC) stage IIIA-N2 is one of the most rigorously debated controversies [1, 2].